Mirogabalin for Central Neuropathic Pain After Spinal Cord Injury: A Randomized, Double-Blind, Placebo-Controlled, Phase 3 Study in Asia. (14th March 2023) - Ushida, Takahiro; Katayama, Yoichi; Hiasa, Yoichi; Nishihara, Makoto; Tajima, Fumihiro; Katoh, Shinsuke; Tanaka, Hirotaka; Maeda, Takeshi; Furusawa, Kazunari; Richardson, Mary; Kakehi, Yoshihiro; Kikumori, Kunika; et al.
Abstract : Background and Objectives: Patients with spinal cord injury (SCI) commonly experience central neuropathic pain (CNeP), which is challenging to treat. Mirogabalin is effective for peripheral neuropathic pain, but evidence for CNeP is lacking. Methods: This randomized, double-blind, placebo-controlled, phase 3 study investigated mirogabalin efficacy and safety for the treatment of CNeP in patients with traumatic SCI. Adult patients from 120 sites throughout Japan, Korea, and Taiwan were randomized (1:1) to receive placebo or mirogabalin (5 mg twice daily [BID] for 1 week, 10 mg BID for 1 week, and 10 or 15 mg BID for 12 weeks). Patients with moderate renal impairment received half the dosage. The primary efficacy endpoint was change from baseline in the weekly average daily pain score (ADPS) at week 14. The secondary endpoints included ADPS responder rates, the Short-Form McGill Pain Questionnaire (SF-MPQ), average daily sleep interference score (ADSIS), and Neuropathic Pain Symptom Inventory (NPSI). Adverse events were monitored for safety. Results: Each treatment group comprised 150 patients. Mirogabalin elicited a statistical and clinically relevant improvement in change from baseline in the weekly ADPS at week 14 (least-squares mean difference [95% CI] vs placebo −0.71 [−1.08 to −0.34], p = 0.0001). Responder rates at week 14 were higher for mirogabalin than those for placebo (odds ratio [95% CI] 1.91 [1.11–3.27] for the ≥30% responder rate; 2.52 [1.11–5.71] for the ≥50% responder rate). Statistical improvements (i.e., least-squares mean difference [95% CI] vs placebo) were also observed in the SF-MPQ (−2.4 [−3.8 to −1.1]), ADSIS −0.71 (−1.04 to −0.38), and NPSI −7.7 (−11.1 to −4.4) scores. Most treatment-emergent adverse events were mild; no serious adverse drug reactions were reported. Discussion: Mirogabalin elicited clinically relevant decreases in pain and was well tolerated, suggesting that mirogabalin is a promising treatment for patients with CNeP due to SCI. Trial Registration Information: ClinicalTrials.gov (NCT03901352); first submitted April 3, 2019; first patient enrolled March 14, 2019; available at clinicaltrials.gov/ct2/show/NCT03901352 . Classification of Evidence: This study provides Class I evidence that in adult patients with CNeP due to traumatic SCI, mirogabalin, 10 or 15 mg BID, effectively improves weekly ADPS at week 14.